Experimental and Numerical Study of the Interfacial Shear Strength in Carbon Fiber/Epoxy Resin Composite under Thermal Loads - Hongxiao Wang; Xiaohui Zhang; Yugang Duan; Lingjie Meng (International Journal of Polymer Science)
This study examined the influence mechanism of temperature on the interfacial shear strength (IFSS) between carbon fiber (CF) and epoxy resin (EP) matrices under various thermal loads using experimental and numerical simulation methods. To evaluate the change in IFSS as a function of the increase in temperature, a microbond test was performed under controlled temperature environment from 23°C to 150°C. The experimental results showed that IFSS values of CF/EP reduce significantly when the temperature reaches near glass transition temperature. To interpret the effect of thermal loads on IFSS, a thermal-mechanical coupling finite element model was used to simulate the process of fiber pull-out from EP. The results revealed that temperature dependence of IFSS is linked to modulus of the matrix as well as to the coefficients of thermal expansion of the fiber and matrix.